Methyl-β-cyclodextrin Suppresses Hyaluronan Synthesis by Down-regulation of Hyaluronan Synthase 2 through Inhibition of Akt - Kultti, Anne (American Society for Biochemistry and Molecular Biology, 2010)
Hyaluronan synthases (HAS1–3) are integral plasma membrane proteins that synthesize hyaluronan, a cell surface and extracellular matrix polysaccharide necessary for many biological processes. It has been shown that HAS is partly localized in cholesterol-rich lipid rafts of MCF-7 cells, and cholesterol depletion with methyl-β-cyclodextrin (MβCD) suppresses hyaluronan secretion in smooth muscle cells. However, the mechanism by which cholesterol depletion inhibits hyaluronan production has remained unknown. We found that cholesterol depletion from MCF-7 cells by MβCD inhibits synthesis but does not decrease the molecular mass of hyaluronan, suggesting no major influence on HAS stability in the membrane. The inhibition of hyaluronan synthesis was not due to the availability of HAS substrates UDP-GlcUA and UDP-GlcNAc. Instead, MβCD specifically down-regulated the expression of HAS2 but not HAS1 or HAS3. Screening of signaling proteins after MβCD treatment revealed that phosphorylation of Akt and its downstream target p70S6 kinase, both members of phosphoinositide 3-kinase-Akt pathway, were inhibited. Inhibitors of this pathway suppressed hyaluronan synthesis and HAS2 expression in MCF-7 cells, suggesting that the reduced hyaluronan synthesis by MβCD is due to down-regulation of HAS2, mediated by the phosphoinositide 3-kinase-Akt-mTOR-p70S6K pathway.